GD2-targeting therapy: a comparative analysis of approaches and promising directions - Philippova, Julia; Shevchenko, Julia; Sennikov, Sergey (Frontiers in Immunology, 2024)
Disialoganglioside GD2 is a promising target for immunotherapy with expression primarily restricted to neuroectodermal and epithelial tumor cells. Although its role in the maintenance and repair of neural tissue is well-established, its functions during normal organism development remain understudied. Meanwhile, studies have shown that GD2 plays an important role in tumorigenesis. Its functions include proliferation, invasion, motility, and metastasis, and its high expression and ability to transform the tumor microenvironment may be associated with a malignant phenotype. Structurally, GD2 is a glycosphingolipid that is stably expressed on the surface of tumor cells, making it a suitable candidate for targeting by antibodies or chimeric antigen receptors. Based on mouse monoclonal antibodies, chimeric and humanized antibodies and their combinations with cytokines, toxins, drugs, radionuclides, nanoparticles as well as chimeric antigen receptor have been developed. Furthermore, vaccines and photoimmunotherapy are being used to treat GD2-positive tumors, and GD2 aptamers can be used for targeting. In the field of cell therapy, allogeneic immunocompetent cells are also being utilized to enhance GD2 therapy. Efforts are currently being made to optimize the chimeric antigen receptor by modifying its design or by transducing not only αβ T cells, but also γδ T cells, NK cells, NKT cells, and macrophages. In addition, immunotherapy can combine both diagnostic and therapeutic methods, allowing for early detection of disease and minimal residual disease. This review discusses each immunotherapy method and strategy, its advantages and disadvantages, and highlights future directions for GD2 therapy.